Your Foundation in Health & Social Care - Brotherton, Graham; Parker, Steven (London : SAGE Publications Ltd, 2013)
Your Foundation in Health & Social Care provides readers with all the knowledge and skills necessary for effective learning at Foundation level, both in study and the workplace. It explores all the key areas of the Foundation degree, including values, communication, legal issues and psychology.
About the Editors and Contributors Introduction -- Graham Brotherton and Steven Parker PART ONE: APPROACHES/Approaching Learning -- Ruth Beretta Learning through Work and Placement: Becoming Reflective -- Graham Brotherton, Helen Davies, Gill McGillivray and Steven Parker Understanding Evidence and Information; Becoming Research Aware -- Graham Brotherton PART TWO: KEY ISSUES The Social Context of Health and Social Care -- Robert Mears Developing a Professional Identity -- Graham Brotherton and Gill McGillivray Values in Practice -- Steven Parker The Political and Organisational Context of Health and Social Care -- Graham Brotherton Psychology for Health and Social Care -- Nadine Pearce Interpersonal Communication -- Judith Mann The Future of Health and Social Care Services -- Graham Brotherton Glossary Bibliography Index
Includes bibliographical references and index.
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
WorldCat record variable field(s) change: 650
Keywords: Social service; Medical care; Vocational guidance; Medical personnel -- Training of; Social Work -- education; Education, Professional -- organization & administration; Health Personnel -- education; Vocational Guidance; Social Work; Patient Care; vocational guidance; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; United Kingdom